Cross Section Measurements of Neutron Induced Reactions on Mo Isotopes - Bari, Zoi; Michalopoulou, Veatriki; Vlastou, Roza; Diakaki, Maria; Kokkoris, Michael; Axiotis, Michail; Lagoyannis, Anastasios; Nicolis, Nikolaos G.; Kopanos, Sotirios Alexandros; Giannakou, Nikoletta; Pouris, Nikos (HNPS Advances in Nuclear Physics, 2026)
The cross section of the 100Mo(n, 2n)99Mo reaction has been measured with the activation technique and 27Al(n, α)24Na as reference reaction, at 16.0 MeV and 14.6 MeV. Both energies were achieved at N.C.S.R. “Demokritos” during the same irradiation, placing the target assembly both at 0° and 80° with respect to the main neutron beam, which was produced via the 3H(d, n)4He reaction. In this work, the neutron production at 14.6 MeV was thoroughly investigated experimentally and via Monte Carlo simulations with the MCNP6 code, as it was used for the first time at N.C.S.R. “Demokritos” for cross section measurements. Two simulations were carried out: the first one to study energy variations with laboratory angle, and the second to replicate this specific experiment using a 2.15 MeV deuteron beam and targets positioned at 0° and 80°, corresponding to neutron energies of 16.0 MeV and 14.6 MeV respectively. Both 100Mo(n, 2n)99Mo and 27Al(n, α)24Na reactions were employed to validate the simulation results. Good agreement between simulation and experiment demonstrates that the approach reliably reproduces both the angular and energy characteristics of the neutron beam, providing a foundation for further studies at additional neutron energies and angles.